Afterglow of atmospheric non-thermal plasma for disinfection of lentil seeds from Botrytis Grey Mould. (December 2020) - Taheri, Saeedeh; Brodie, Graham Ian; Gupta, Dorin; Jacob, Mohan V.
Abstract: Seed-borne fungal diseases of grains are a serious threat to grain crops' yield due to lack of either resistant crop varieties or dependence on fungicides. Therefore, there is a growing demand to develop sustainable technologies for crop protection. In the present study, an atmospheric microwave plasma was employed to eradicate Botrytis cinerea from lentil seeds. Argon, air and a combination of them were applied to create the plasma. There was a 41% reduction in the percentage of artificially contaminated seeds (with an initial contaminated seed percentage of 95.8%) after 100 s treatment of 2.5 g of lentil seeds with the afterglow of air plasma followed by 24-h holding time. A 32.3% reduction occurred when a 30% air/70% Argon was applied for 10 s and 60 min of holding time. The holding time of 24 h increased catalase activity from 0.8 to 1.1 mM H2 O2 mg −1  min −1 that was an indicator of early plant immune system fortification. This also changed seeds' colour toward redness and yellowness. Conclusively, the afterglow of microwave plasma could be considered as a part of integrated disease management in lentil crops. Highlights: Lentil's infection with BGM reduced by 41% of inoculated seeds using the afterglow of air plasma. A holding in the processed gas after treatments increased infection reduction. Catalase activity of lentil seed was slightly triggered after 24 h of holding time. Seed wettability increased and their colour changed after 24 h of holding time.